Influence of the heteroatom on the optoelectronic properties and transistor performance of soluble thiophene-, selenophene- and tellurophene–vinylene copolymers. Issue 2 (12th November 2015) - Al-Hashimi, Mohammed; Han, Yang; Smith, Jeremy; Bazzi, Hassan S.; Alqaradawi, Siham Yousuf A.; Watkins, Scott E.; Anthopoulos, Thomas D.; Heeney, Martin
Abstract : We report the first soluble poly(3-dodecyl tellurophenylenevinylene) and compare its properties to the analogous thiophene and selenophene containing polymers. Abstract : We report the first soluble poly(3-dodecyl tellurophenylene-vinylene) polymer (P3TeV ) by Stille copolymerization and compare its properties to the analogous thiophene and selenophene containing polymers. The optical band gap of the polymers is shown to systematically decrease as the size of the heteroatom is increased, mainly as a result of a stabilization of the LUMO energy, resulting in a small band gap of 1.4 eV forP3TeV . Field effect transistors measurements in variety of architectures demonstrate that the selenophene polymer exhibits the highest mobility, highlighting that increasing the size of the heteroatom is not always beneficial for charge transport.